Probing neutrino mass with multilepton production at the Tevatron in the simplest R-parity violation model (2003)
ABSTRACT: We analyse the production of multileptons in the simplest supergravity model with bilinear violation of R parity at the Fermilab Tevatron. Despite the small R-parity violating couplings needed to generate the neutrino masses indicated by current atmospheric neutrino data, the lightest supersymmetric particle is unstable and can decay inside the detector. This leads to a phenomenology quite distinct from that of the R-parity conserving scenario. We quantify by how much the supersymmetric multilepton signals differ from the R-parity conserving expectations, displaying our results in the m0 x m1/2 plane. We show that the presence of bilinear R-parity violating interactions enhances the supersymmetric multilepton signals over most of the parameter space, specially at moderate and large m0.